Reproductive Biology of Cork Fish (Channastriata Bloch, 1793) in SeiPaku Reservoir, Sub-District Kampar Kiri, Kampar Districts, Riau Province - Mariani Silvia Br Sihombing; Deni Efizon; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Cork fish (Channastriata) is one of the freshwater fish species that live in the SeiPaku Reservoir. This study aims to determine the reproductive biology of cork fish, carried out in February-April 2019. Fish sampling is carried out 6 times at one-time interval in 2 weeks. The parameters measured were sex ratio, gonadal maturity level, Gonad Maturity Index (IKG), fecundity and egg diameter. The total sample of 97 fish, consisted of 54 male and 43 female, and a sex ratio of 1:1. Male cork fish develop gonads at a size of 364 mm (TL), while female cork fish begin to develop gonads at a size of 311 mm (TL). Male cork fish are at the level of gonadal maturity (TKG) I, II, III and IV, and female cork fish are also at the level of gonadal maturity (TKG) I, II, III and IV. Male fish IKG ranges from 0.01% -1.05%, while female fish ranges from 0.04% -3.42%. The fecundity of cork fish ranges from 27,374-54,248 grains and egg diameter 0.8-1.1 mm. Keywords: Sex ratio, gonadal maturity level, gonadal maturity index, fecundity